Levator ani muscle coactivation at term is associated with longer second stage of labor in nulliparous women. (2nd April 2019) - Youssef, A.; Montaguti, E.; Dodaro, M. G.; Kamel, R.; Rizzo, N.; Pilu, G.
ABSTRACT: Objective: To assess the effect of levator ani muscle (LAM) coactivation at term on outcome of labor in nulliparous women. Methods: This was a prospective study of 284 low‐risk nulliparous women with a singleton pregnancy at term recruited before the onset of labor. The anteroposterior diameter of the levator hiatus was measured in each woman on transperineal ultrasound at rest, on maximum pelvic floor muscle contraction and on maximum Valsalva maneuver before and after visual feedback. LAM coactivation was defined as a reduction in the anteroposterior diameter of the levator hiatus on maximum Valsalva maneuver in comparison with that at rest. The association of pelvic hiatal diameter values and LAM coactivation with mode of delivery and duration of labor was assessed. Results: No significant difference was found between women who underwent Cesarean delivery and those who had a vaginal delivery with regard to the anteroposterior diameter of the levator hiatus at rest, on pelvic floor muscle contraction and on Valsalva maneuver. Longer second stage of labor was associated with shorter anteroposterior diameter of the levator hiatus on all assessments, but in particular at rest and on Valsalva both before and after visual feedback. LAM coactivation was found in 89 (31.3%) and 75 (26.4%) women before and after visual feedback, respectively. Post visual feedback, women with LAM coactivation had a significantly longer second stage of labor than did those without LAM coactivation (83 ± 63 vs 63 ± 42 min; P = 0.006). On Cox regression analysis, LAM coactivation post visual feedback was an independent predictor of longer second stage of labor (adjusted hazard ratio, 1.499 (95% CI, 1.076–2.087); P = 0.017). Conclusion: LAM coactivation in nulliparous women at term is associated with a longer second stage of labor. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.